2019
DOI: 10.17547/kjsr.2019.27.4.404
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Emotional Labor, Professional Self-Concept, Self-Efficacy & Social Support of Emergency Room Nurse’s Burnout

Abstract: Background: The purpose of this study was to investigate the effects of emotional labor, professional self-concept, self-efficiency and social support on burnout of emergency room nurses by verifying the level of burnout of them. Through this, we will reduce the turnover and secure professional manpower and they will provide basic data on efficient manpower management. Methods: The subjects of this study were 130 emergency room nurses of eight hospitals in Seoul. The collected datas were analyzed by the SPSS V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
10
1
2
Order By: Relevance
“…In comparing self-efficacy in nurses, it was found that GSE determined using the original tool (SGSES; M = 3.42, SD = 0.50) was slightly higher than nursing profession self-efficacy determined using the K-NPSES ( M = 3.3, SD = 0.43). In addition, the results of the SGSES were found to be relatively higher than those reported in the studies of Chegini et al (2019; M = 3.55, SD = 0.45), De Simone et al (2018; M = 3.71, SD = 0.47), and M. Kim et al (2019; M = 3.56, SD = 0.48), which may be attributed to the selection and exclusion criteria used in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…In comparing self-efficacy in nurses, it was found that GSE determined using the original tool (SGSES; M = 3.42, SD = 0.50) was slightly higher than nursing profession self-efficacy determined using the K-NPSES ( M = 3.3, SD = 0.43). In addition, the results of the SGSES were found to be relatively higher than those reported in the studies of Chegini et al (2019; M = 3.55, SD = 0.45), De Simone et al (2018; M = 3.71, SD = 0.47), and M. Kim et al (2019; M = 3.56, SD = 0.48), which may be attributed to the selection and exclusion criteria used in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…Most of the emergency room nurses who participated in this study were unmarried in their early 30s, and most of them had less than 3 years of experience in the emergency room. Considering that more than half of the emergency room nurses have less than 3 years of experience, it can be seen that work stress related to emotional labor is high [ 21 , 22 ]. Therefore, continuous and effective management is needed to improve the nursing work environment, reduce the work stress of emergency room nurses, and provide psychological stability.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is thus deemed an important personal resource with which one can cope with job stress. Therefore, an increase in perceived self-efficacy may enable employees to view emotional labor as a means to an end (i.e., rewards and recognition) rather than a stressful act [50,51]. Thus, the following hypotheses are proposed (Figure 1): Hypothesis 8 (H8).…”
Section: Self-efficacy and Its Mediating Rolementioning
confidence: 99%